Cross-informant consistency between parents and teachers of children and adolescents on externalizing and internalizing problems. - Tay, Yi Ling. (2009)
An archival, cross-sectional study was implemented to investigate cross-informant consistency for externalizing and internalizing problems between parents and teachers, relationships between children’s age and level of agreement, and length of time teachers had known the children and level of agreement. Results showed that agreement was higher on externalizing than internalizing problems, and of boys on externalizing problems. Level of agreement between informants was found to increase as the child grew older for externalizing problems, while no relationship was found for internalizing problems, and similarly, between the length of time the teachers had known the children and level of agreement. Implications and suggestions for future research are discussed.